BCG Tuberculosis Vaccine: Immunological and Clinical Efficacy in Children Born to HIV-Infected Women - N. I. Klevno; V. A. Aksenova (Биопрепараты: Профилактика, диагностика, лечение)
The article analyses the efficacy of vaccination and its influence on the nature of tuberculosis process in children perinatally exposed to  HIV. The study analysed hospital records, hospital discharge  summaries and outpatient medical records of children under 14 with  tuberculosis: there were 109 HIV-infected children and 97 children  perinatally exposed to HIV (but not HIV-infected). The postvaccinal  immunity status was assessed by the presence and size of the  vaccination scar and the response to the Mantoux test. The clinical  efficacy of the BCG vaccination was assessed by the severity of  tuberculosis in vaccinated and non-vaccinated children. It was shown that immunization with BCG vaccine (BCG-M) was safe and  efficacious in children born to HIV-infected women but not infected  with HIV. At the same time the vaccine did not demonstrate  sufficient immunological and clinical efficacy in HIV-infected children: the response to the Mantoux test, 2 TU, was positive only in one  third of all vaccinated children; there was no statistically significant  difference in the frequency of disseminated processes in vaccinated children as compared to the non-vaccinated children  perinatally exposed to HIV. A conclusion was made that children born to HIV-infected mothers but not infected with HIV must be  vaccinated during the neonatal period. The vaccination of HIV- infected children is not advisable due to its low clinical efficacy and  the risk of development of disseminated complications, for instance,  the generalized BCG infection in HIV-infected children may develop over a period of 3 years after vaccination.